(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Jawadullah, Akhtar N. 2023. Short Communication: Ethnobotanical survey of medicinal plants for wound-healing in Dir Upper District, Pakistan. Asian J Ethnobiol 6: 145-152. Medicinal plants have been used since ancient time by the communities as an alternative to the synthetic medicine, which have adverse side effects and is not available to every individual. This study reports medicinal plants used for wound-healing by the local peoples in Dir Upper District, northern area of Pakistan. A semi-structured questionnaire was used to collect ethnomedicinal data by interviewing 50 informants of different ages (25 to 90 years old). Plant samples were collected as herbarium to be identified in the laboratory. The result shows a total of 20 plant species, each belonging to different families, were used for wound-healing. The majority of growth forms of such plants were herbs (35%) and trees (35%), followed by shrubs (25%) and climbers (5%). The plant parts used for healing were leaves of the plant (45%), followed by plant bark (10%), whole plant (10%), plant roots (10%), fruit peel (5%), gum (5%), bulb (5%), rhizome (5%) and latex (5%). Furthermore, external applications were more common than oral consumption to promote wound-healing. Berberis lycium Royle, Curcuma longa L. and Punica protopunica Balf.fil. were the most cited species used to heal wounds. This study revealed that there is an array of plant biodiversity among Pakistanis for the purpose of wound-healing. This is a result of the socioeconomic status and limited access to modern health services and their preference for folk medicine. Further studies should be planned to create an online database for a collection of therapeutic medicinal plants and their traditional healing potentials.